Speed and countermovement-jump characteristics of elite female soccer players, 1995-2010 - Haugen, T. A.; Tonnessen, E.; Seiler, S. (International Journal of Sports Physiology and Performance, 2012)
Purpose: The purpose of this investigation was to compare sprint and countermovement-jump (CMJ) performance among female competitive soccer players as a function of performance level, field position, and age. In addition, the authors wanted to quantify the evolution of these physical characteristics among elite players over a 15-y period. Methods: 194 female elite players (22± 4.1 y, 63 ± 5.6 kg), including an Olympic winning squad, tested 40-m sprint with electronic timing and CMJ on a force platform at the Norwegian Olympic training center from 1995 to 2010. Results: Moderate to large velocity differences across performance levels and positions were observed. National-team players were 2% faster than 1st-division players (P = .027, d = 0.5) and 5% faster than 2nd-division players (P < .001, d = 1.3) over 0-20 m. National-team players jumped 8-9% higher than 1st-division players (P = .001, d = 0.6) and junior elite players (P = .023, d = 0.5). Forwards were 3-4% faster than midfielders (P < .001, d = 0.8) and goalkeepers (P = .003, d = 0.9) over 0-20 m. No differences in velocity or CMJ height were observed among the age categories. Players from 2006-2010 were 2% faster (P < .05, d = 0.6) than players from 1995-1999 over 20 m, whereas no differences in 20- to 40-m velocity or CMJ performance were observed. Conclusions: This study provides effect-magnitude estimates for the influence of performance level, age, and player position on sprint and CMJ performance in female soccer players. While 20- to 40-m velocity and CMJ performance have remained stable over the time, there has been a moderate but positive development in 0- to 20-m velocity among elite performers.